ANALISIS PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SMP - Pratiwi Putri Hediana; Tutut Nurita (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
Science process skills are competencies that students can build their own concepts learned. The purpose of this study was to analyze the use of guided inquiry learning models to improve science process skills for science subjects in junior high school students. This research uses qualitative research, descriptive method. The research sample was 30 junior high school students and data collection was carried out by observation, interviews, and distributing questionnaires. The results showed that the use of guided inquiry learning in science learning was able to improve students' science process skills. This can be seen in the guided inquiry learning model which is a student-centered learning process. With this, students independently seek solutions to a problem with the supervision of the teacher. The results of the questionnaire analysis showed that there was an increase in the percentage of indicators of students' science process skills. The average increase experienced is from 49.33% to 76.66%. The improvement of science process skills in students can be formed and developed with habits that are carried out continuously in the learning process, in order to improve scientific understanding.